FACTORS THAT AFFECT STUDENTS' MATHEMATICS PERFORMANCE AT HIGHER EDUCATION IN RIAU PROVINCE DURING THE COVID-19 PANDEMIC - Nofriyandi Nofriyandi; Dedek Andrian (Jurnal Infinity, 2022)
This study aims to determine the factors influencing the students' mathematics performance in higher education in Riau Province. The research population was all students in higher education in Riau Province majoring in mathematics. The samples of this research were some students in higher education majoring in mathematics education which were taken randomly with a proportional random sampling approach. The instrument in this research was a questionnaire developed and validated by experts and distributed to mathematics education students. The data analysis used in this research was path analysis. The results showed that there was an effect of learning motivation on mathematics performance, there was no effect of learning interest on mathematics performance, with a T Value of 1.28, (12) there was no effect of self-efficacy on mathematics performance, with T Values of 1.38, there was an effect of self-regulated on mathematics performance, with T Values of 2.23, and (15) there was no effect of learning involvement on mathematics performance, with T Value of 1.39 The dominant and significant factor in influencing the students' mathematics performance in higher education in Riau province during the COVID-19 Pandemic was learning motivation and self-regulation.